Tekanan Fiskal, Kapabilitas Internal Audit, dan Penyerapan Anggaran Pemerintah Daerah di Indonesia - Fitri Fitri; Rosmayanti Rosmayanti; Arsheilla Tiara Rahayudhy; Vivi Novila Dachi; Hani Kustyanti Kusnadi; Verna Budi Amanda; Muhammad Imaduddin Putranda; Elok Faiqoh Himmah (Indonesian Accounting Literacy Journal, 2026)
This study examines the influence of fiscal pressure and internal audit capability on budget absorption in district and city governments in Indonesia. Recurring failures to achieve the 100% budget absorption target represent a significant public sector challenge, as low absorption weakens public service quality and hinders regional economic growth. Grounded in Stewardship Theory, which emphasizes responsible management and effective internal oversight, this study uses secondary data from BPKP Performance Reports, regional budget documents, and budget realization reports for 2018–2022. Panel data regression analysis via SPSS was employed to test the hypotheses. Results indicate that fiscal pressure negatively and significantly affects budget absorption, while internal audit capability has a positive and significant effect. Simultaneously, both variables significantly influence budget absorption, providing empirical evidence that strong internal oversight is essential for improving local government budget implementation effectiveness.